Contrasting nutrient utilization strategies of dominant tree species in representative artificial and natural forests on the coastal sandy land of northern Hainan Island - Jia, Junting; Chen, Yiqing; Chen, Zongzhu; Su, Shaofeng; Lin, Zhipan; Lei, Xiangling; Chen, Haihui; Nong, Shouqian (Frontiers in Plant Science, 2025)
The nutrient content of plant leaves serves as a critical indicator of nutrient uptake efficiency, thereby reflecting plant nutrient utilization strategies. Previous studies have primarily focused on nutrient cycling within individual forest ecosystems or the effects of management practices in artificial forests, with limited comparative analysis between artificial and natural forests. In this study, the dominant tree species in typical artificial forest and natural forest in the coastal sandy land in the northern part of Hainan Island were taken as the research objects, compared the elemental contents of dominant tree species in different forest types and analyzed the relationships among these elements. The results showed that: (1) the elements of nitrogen, phosphorus, and potassium in the leaves of artificial forest plants in northern Hainan’s coastal sandy land are 10.16%, 24.72% and 25.00% higher than those in the natural forest, respectively; the calcium content in leaves of natural forest plants is significantly higher than those in the artificial forest by 268.94%, and the elements of magnesium in the leaves of plants in the natural forest are higher than those in the artificial forest by 114.76%. (2) The correlation between the concentration of chemical elements of plant leaves in the artificial forests was stronger than that between the concentration of chemical elements of natural forests. N and K show a strong positive correlation. P is significantly positively correlated with K and Mg. Ca is highly correlated with K and Mg. N/P is negatively correlated with P and Mg. (3) Plant samples from the artificial forest had higher scores on variables related to “N” and “P”, while plant samples from the natural forest had higher scores on variables related to “Ca” and “Mg”. Overall, our results suggest that the dominant tree species in artificial forests may adopt a rapid-growth strategy, while the dominant tree species in natural forests may adopt a slow-growth strategy, and the results of this study will provide scientific and technological support for the effectiveness of vegetation restoration and evaluation of tropical coastal sand lands.